Model Pengembangan Lagu PIA “Aku Katolik Aku Percaya” Tema Pengenalan Syahadat Iman Katolik - Bonaventura Omega Kristian Narwastu; Hartutik Hartutik; Timotius Tote Jelahu; Andarweni Astuti (Pengharapan : Jurnal Pendidikan dan Pemuridan Kristen dan Katolik, 2025)
Child faith accompaniment plays a central role in the future development of children’s faith, making it the chosen initial teaching to prepare for a more mature faith development within a tiered faith formation. However, in the context of child faith accompaniment, there is currently no song themed on the Catholic Creed that can be taught to children, including at the Holy Family Parish Atmodirono Semarang, which has never used a song with this theme. This study aims to develop a child faith accompaniment (PIA) song themed on the introduction of the Catholic Creed to provide children with a deeper understanding of the Catholic Creed. The research uses the Research and Development (R&D) method with the ADDIE model (Analyze, Design, Development, Implementation, Evaluation) to analyze the needs of PIA, design the product, conduct trials, and evaluate it to ensure a positive impact on children’s faith education. Initial analysis showed that there was no existing song media introducing the basic Catholic faith in PIA activities. In the design phase, the researcher composed lyrics and melodies relevant to Catholic teachings, using key phrases from the “I Believe” prayer, adjusted to be easily understood by children. The development phase involved a Focus Group Discussion (FGD) with PIA practitioners and music experts. Subsequently, the song was trialed during Minggu Gembira activities and evaluated for improvements. The implementation of the song titled “I am Catholic, I Believe” showed positive impact. Observations revealed that children were enthusiastic, listened attentively, endeavored to understand, memorize, and sing the song together. Evaluation results showed an improvement in scores from 79% to 95.8%. Based on this increase, it can be concluded that the song “I am Catholic, I Believe” is highly effective and can be used as a child faith accompaniment medium to help children understand the meaning of the “I Believe” prayer as the Catholic Creed, as well as strengthen their understanding of the core teachings of Catholicism.